Negative Politeness Strategies in Jordanian EFL Textbook Dialogs: A Content Analysis of Action Pack 5 through 10 - Bataineh, Ruba Fahmi; Salman, Fatima A.; Al.Roumi, Hydaya J; Al.Jawarneh , Rabya Sh; Shkour, Amani G; Okour, Sherin Adnan; Al- Jamal, Dina A. (Journal of Ethnic and Cultural Studies, 2023)
Social, humane and cultural values mandate that a certain level of politeness in day-to-day exchanges be maintained. Therefore, politeness strategies are among the first language functions taught in foreign language curricula. This study examines the inclusion of negative politeness strategies in the dialogs of the prescribed Jordanian English as a foreign language textbook, Action Pack, for grades 5 through ten. The content analysis is informed by the theoretical principles of politeness theory (Brown & Levinson, 1987). The dialogs in the fifth- through tenth-grade textbooks were content analyzed for speech acts denoting negative politeness, using both qualitative and quantitative measures. The analysis commenced with coding, after which the occurrences were identified and tallied per the codes. Ten negative politeness strategies were identified in addition to one, which comprised an amalgamation of two of these strategies in one speech act. The findings revealed that Jordanian Action Pack textbooks included more negative politeness strategies in grades 5 and 6 than in grades 7, 8, 9, and 10, with being indirect and using questions to reduce imposition and offense as the most frequent.